Predictive factors of functional outcome in patients with poor-grade subarachnoid hemorrhage undergoing surgery: our experience in 10 years - Montilla, Flor; Guevara, María; Álvarez Caicedo, Diana Carolina; Martínez, Silvina; Martín, Clara; Rubino, Pablo (Revista Argentina de Neurocirugía, 2025)
Background: subarachnoid hemorrhage (SAH) is a condition associated with high morbidity. High-grade SAH accounts for 20-40% of cases. Due to the high mortality rate in this subgroup, the role of surgical treatment remains controversial. Objective: to analyzes a series of patients with high-grade aneurysmal SAH and evaluate variables that may influence functional outcomes. Methods: a single-center, analytical, retrospective study of a cohort of surgical patients with high-grade SAH over a 10-year period, with a minimum follow-up of six months. Demographic, clinical, imaging, anatomical, and surgical variables were analyzed. Clinical outcomes were categorized using the modified Rankin Scale (mRS) as either favorable or poor. The results were compared with data from existing literature. Results: a total of 90 patients diagnosed with high-grade SAH who underwent surgical intervention were included. The mean age at diagnosis was 42 years, and 56% were female. Hematoma was present in 45.5% of cases, hydrocephalus in 17.7%, and edema in 32.6%. Twenty-three patients presented with pupillary abnormalities, and rebleeding occurred in 21 patients. A poor functional outcome was statistically associated with Hunt & Hess grade V and age over 60 years. Increased mortality was correlated with advanced age (>60 years) and pupillary abnormalities. Overall mortality was 57.7%, while a favorable outcome with an independent lifestyle was achieved in 26% of patients. Conclusion: high-grade SAH is associated with high morbidity and mortality. Hunt & Hess grade V and age over 60 years were predictors of poor outcomes. Surgical treatment is justified in the subset of patients who achieve an independent lifestyle.